Metodologia de gestão do trabalho em saúde e a qualidade da assistência pré-natal e seus desfechos perinatais no município de Vitória, Espírito Santo - Ruschi, Gustavo Enrico Cabral (2018)
The computerization of health and the implementation of Matrix Support (AM) in Women's Health are normative work processes adopted in the city of Vitória, Espírito Santo (ES), aiming to qualify and increase the resolubility of professionals inserted in the context of Primary Health Care (APS). Objectives: To evaluate the quality dimensions of data from patients' electronic patient records (PEP) followed in the APS of Vitória-ES, the influence of MA in determining the quality of prenatal care and to understand its effect on the determination of adverse perinatal outcomes. Material and Methods: Two cross sectional studies were carried out, with a quantitative approach, from a representative sample, previously calculated and randomly selected from the records of pregnant women enrolled in the basic health care units of Vitória, Espírito Santo, between January 2013 and December (coverage, non-duplicity, accessibility, timeliness, methodological clarity, completeness, consistency and reliability); the second analyzed the quality of prenatal care based on the number of visits, prenatal start, clinicalobstetric procedures and laboratory tests performed. The third study is a cohort with multilevel hierarchical analysis of records of newborns from mothers followed-up in the APS of Vitória-ES, during the same period from 2013 to 2014, evaluating adverse perinatal outcomes (prematurity, low birth weight and early neonatal death). Results: In the evaluation of the data quality dimensions of the PEP, prenatal coverage, considering the onset of prenatal care, was 80%. Despite the restriction of access, opportunity and lack of methodological clarity, the clinical record showed excellent consistency and completeness in the fields of obstetric procedures and laboratory tests. Reliability showed disagreements with the Live Birth Information System. When analyzing the quality of prenatal care, there is a decrease in the adequacy of care provided as the level of analysis becomes more complex. The variables that showed an association with the non-adequacy of care quality were: greater number of children (OR=0.63; IC=0.44-0.92), gestational risk (OR=1.86; IC95%=1.02-3.38) and absence of matrix support (OR=1.50; IC95%=1.10-2.06). The hierarchical analysis model inferred that the chance of a pregnancy to progress to an adverse perinatal outcome increases the higher the number of previous pregnancies (OR=4.39; IC95%=1,93-10,0) and the lower number of prenatal consultations performed (OR=4,99; IC95%=2,18-11,42). No effect of MA on outcomes was observed. Conclusions: There is potential of the electronic medical record as a source of epidemiological information on prenatal care. However, the data suggest that the presence of the Matrix Support does not significantly influence the completeness of the medical record. Greater emphasis on completing medical records and integrating with other levels of care is necessary. The implantation and valorization of strategies of reorganization of services and practices, such as AM, are determinants of quality improvement in prenatal care, and it is necessary to increase the degree of support. Although the proposed hierarchical model demonstrates direct determination of sociodemographic and obstetric characteristics on adverse outcomes, the particular characteristics of PHC in the city of Vitoria-ES reduce the positive effects of AM.